(untitled) (International Journal of Atharva, 2024)
This review article validates how gender is constructed through the activities of both males’ and females’ everyday life and provides the sufficient replies for them who always ask how the gender is socially created. In accordance to the various references - a case study, secondary data and systematic literature review along with content analysis method is applied to verify the creation of gender, and gender roles in every society from their performances. Gender is not the issue of certain society but the matter of global society, remains as an element of inequality on various situations and this study seeks more evidences which justify how gender is socio-culturally assembled. Gender roles change in relation to sex gradually and nowadays, technological developments engross gender roles on another level. The roles accomplished by females in previous societies were initiated to be done by males and vice versa. Therefore, what activities males alongside females perform within and outside households according to their needs; and how those activities contribute to creating new gender roles in their own and in the global society have been assessed. Hence, the article finally concludes that gender is a relative social product, and is constructed due to the role performances according to the norms and values of a particular society on the basis of sex differences.